The analysis of innovation input - output relationships in EU member states - Kijek, Arkadiusz; Kijek, Tomasz (Comparative Economic Research. Central and Eastern Europe, 2010)
This article presents some findings of an analysis of innovation input - output relationship in EU member states. The first section of the paper considers the role of innovation in economic growth with particular attention to the new endogenous growth models. In the second part, the dichotomous approach to innovation and its measures is presented. The last section contains the methodology and outcome of research. The results of the study show that R&D expenditures, ICT and human capital are the key innovation inputs that affect such innovation outputs as innovation and patent propensity and new-to-market sales.